Do IMF-Supported Programs Help Make Fiscal Adjustment More Durable? - Moon, Soojin (IMF Working Papers; Working Paper ;, 2003)
This paper investigates fiscal developments in 112 countries during the 1990s. It finds that, while the overall fiscal balance improved in most of them, the composition of this improvement differed. In nonprogram countries, revenues increased modestly and expenditure declined sharply, while in program countries both revenue and expenditure declined. However, in countries with programs that included structural conditions the adjustment was effected primarily through sharp expenditure compression. We did not find evidence of a statistically significant impact of IMF conditionality. Morever, fiscal improvements are strongly influenced by cyclical factors.